Internal training and match load quantification of one-match week schedules in female first league Portugal soccer team - Fernandes, R. (2021)
Training load (TL) quantification allow coaches to a better load management during training sessions to be in the best physical fitness to the next match. The aim of this study was to compare session rated of perceived exertion (sRPE) and Hooper Index (HI) between training and match days from the same women’s Portuguese League team. Sixteen players with a mean±SD age, height and weight of 24.0±2.9 years, 164±4.1 cm and 58.5±8.2 kg, respectively, participated in this study. The participants completed ≥80% of the training sessions during 2019/20 in-season. Data was collected through the s-RPE and the HI that measured sleep quality, fatigue, stress, and muscle soreness (DOMS). Data was analysed in relation to the number of days away from the competitive one-match week (i.e., match day minus, MD-) with three training sessions a week (MD-5; MD-4; MD-2). The study analysed data from a total of 12 matches and 45 training sessions with repeated measures ANOVA, p≤0.05. Results showed differences between MD- 5 (85.2±0.3min) vs MD-4 (87.2±0.4min) vs MD-2 (80.6±0.6min) vs MD (62.8±4.9min), all p<0.05; s-RPE showed higher values on MD-5 (503.8±19.0au) vs MD-4 (473.2±14.8au) vs MD-2 (362.1±12.1au) vs MD (468.2±40.5au); HI showed higher values on MD-5 (13.4±0.5au) vs MD-4 (13.4±0.4au) vs MD-2 (12.7±0.5au) vs MD (11.9±0.4au); DOMS revealed difference between MD-4 vs MD-2 (3.1±0.2 vs 2.7±0.2au), p<0.05. It was shown that there is a higher TL on MD-5 and MD-4 compared with MD-2. Results from HI showed that sleep, fatigue, stress and DOMS was well fair controlled by coaches and staff.